On the tear proteome of the house mouse (Mus musculus musculus) in relation to chemical signalling - Stopkova, Romana; Klempt, Petr; Kuntova, Barbora; Stopka, Pavel (PeerJ, 2017)
Mammalian tears are produced by lacrimal glands to protect eyes and may function in chemical communication and immunity. Recent studies on the house mouse chemical signalling revealed that major urinary proteins (MUPs) are not individually unique in Mus musculus musculus. This fact stimulated us to look for other sexually dimorphic proteins that may-in combination with MUPs-contribute to a pool of chemical signals in tears. MUPs and other lipocalins including odorant binding proteins (OBPs) have the capacity to selectively transport volatile organic compounds (VOCs) in their eight-stranded beta barrel, thus we have generated the tear proteome of the house mouse to detect a wider pool of proteins that may be involved in chemical signalling. We have detected significant male-biased (7.8%) and female-biased (7%) proteins in tears. Those proteins that showed the most elevated sexual dimorphisms were highly expressed and belong to MUP, OBP, ESP (i.e., exocrine gland-secreted peptides), and SCGB/ABP (i.e., secretoglobin) families. Thus, tears may have the potential to elicit sex-specific signals in combination by different proteins. Some tear lipocalins are not sexually dimorphic-with MUP20/darcin and OBP6 being good examples-and because all proteins may flow with tears through nasolacrimal ducts to nasal and oral cavities we suggest that their roles are wider than originally thought. Also, we have also detected several sexually dimorphic bactericidal proteins, thus further supporting an idea that males and females may have adopted alternative strategies in controlling microbiota thus yielding different VOC profiles.
Keywords: Darcin; OBP; Tears; Secretoglobins; Lipocalins; Mus musculus musculus; Pheromone; Toxic waste hypothesis; MUP; Sex dimorphism